2016
DOI: 10.15252/emmm.201606646
|View full text |Cite
|
Sign up to set email alerts
|

The RAS ‐related GTP ase RHOB confers resistance to EGFR ‐tyrosine kinase inhibitors in non‐small‐cell lung cancer via an AKT ‐dependent mechanism

Abstract: Although lung cancer patients harboring EGFR mutations benefit from treatment with EGFR‐tyrosine kinase inhibitors (EGFR‐TKI), most of them rapidly relapse. RHOB GTPase is a critical player in both lung carcinogenesis and the EGFR signaling pathway; therefore, we hypothesized that it could play a role in the response to EGFR‐TKI. In a series of samples from EGFR‐mutated patients, we found that low RHOB expression correlated with a good response to EGFR‐TKI treatment while a poor response correlated with high R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…RhoB may be a tumor suppressor as its expression level is decreased in a number of tumor cell types ( 25 ). Its expression is more downregulated in increasingly aggressive tumors, and the loss of RhoB is associated with a decreased overall survival time in certain types of cancer ( 26 28 ). RhoB is not mutated in all types of cancer; however, its altered expression and activity may be critical in cancer progression and the response to therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RhoB may be a tumor suppressor as its expression level is decreased in a number of tumor cell types ( 25 ). Its expression is more downregulated in increasingly aggressive tumors, and the loss of RhoB is associated with a decreased overall survival time in certain types of cancer ( 26 28 ). RhoB is not mutated in all types of cancer; however, its altered expression and activity may be critical in cancer progression and the response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…RhoB is not mutated in all types of cancer; however, its altered expression and activity may be critical in cancer progression and the response to therapy. For example, RhoB expression is predictive of an epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) response; a EGFR-TKI/Akt inhibitor combination provides a clinical advantage in preventing resistance to EGFR-TKI for RhoB-positive tumor patients ( 26 ). A number of studies have identified a loss of RhoB expression in head, neck, gastric, renal and lung cancer ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumors were analyzed from patients with EGFR mutations and treated with EGFR TKIs. Seventy-five patients were being treated at Toulouse University Hospital (52), and 4 had participated in the MOSCATO (NCT01566019) or MATCH-R (NCT02517892) clinical trials at the Institut Gustave Roussy.…”
mentioning
confidence: 99%
“…Similarly, in RhoB-null vascular smooth muscle cells, PDGF receptor trafficking to the late endosomal compartment and Akt activation were compromised, and this was later shown to also impair Cdc42 and Rac transport to the PM [124,161]. Intriguingly, a recent study also showed that high expression levels of the small GTPase RhoB in non-small-cell lung cancer (NSCLC)conferred resistance to EGFR-TKIs by enhancing Akt activation [162], although it was not investigated whether this was connected to altered EGFR trafficking. Since Akt signaling emanates from both the PM and endomembranes and RhoB is also involved in the nuclear translocation of Akt [163], the precise function of RhoB depends on its location, the available effector proteins and the nature of activated downstream signaling pathways in the cells.…”
Section: Rho Gtpases and Membrane Trafficking-implications For Cancermentioning
confidence: 99%
“…DLC3 was reported to be downregulated in various types of cancers, including breast, prostate, kidney, lung, and ovarian [165]. DLC3 knockdown prevented EGFR degradation and enhanced Akt activation by trapping the receptor in EEA1-positive endosomes [41], making it tempting to speculate that reduced DLC3 expression might also confer EGFR-TKI resistance as described for lung cancers overexpressing RhoB [162]. DLC3 depletion in breast cancer cells also caused aberrant Rab4-dependent matrix metalloproteinase recycling and invadopodia matrix degradation in a RhoB-and actin-dependent manner [41,42,166].…”
Section: Rho Gtpases and Membrane Trafficking-implications For Cancermentioning
confidence: 99%